(untitled) (International Journal of Engineering and Computer Science, 2014)
Students automation system has become more important part for any organizations/ institutions. This paper presents the integration of ubiquitous computing systems in classrooms for managing student’s attendance using RFID. RFID is a powerful tool which helps to manage student’s attendance throughout the working day. RFID is used to solve problems where it is necessary to automatically record the student’s attendance in classrooms of university environment. A real time intelligent system is implemented in conjunction with RFID hardware to record student’s attendance at lectures in a university environment. RFID tag is affixed on identity card to communicate wirelessly with a reader in order to the identify the students